The Formation and Evolution of the Ideology of Domesticity: 1830-1915 - Kuipers, Anne (My University, 2014)
This work splits the nineteenth century into three distinct periods concerning the formation, adoption and revision of the ideology of domesticity as presented through the medium of household manuals. Although a great deal of study has focused on how women interacted with these ideologies, little has been done on researching the way women's actions impacted the ideologies throughout the century. This work concentrates on the ways the ideology evolved over the course of the nineteenth century as female writers responded to different historical events and societal changes. It does not recommend that these ideologies be used in a prescriptive sense, but instead offers a descriptive analysis of nineteenth century household manuals ideological evolution.
Keywords: Women--History--19th century; Home economics--History--19th century; Home economics--Handbooks, manuals, etc.